2010
DOI: 10.1093/brain/awq089
|View full text |Cite
|
Sign up to set email alerts
|

Intonation processing in congenital amusia: discrimination, identification and imitation

Abstract: This study investigated whether congenital amusia, a neuro-developmental disorder of musical perception, also has implications for speech intonation processing. In total, 16 British amusics and 16 matched controls completed five intonation perception tasks and two pitch threshold tasks. Compared with controls, amusics showed impaired performance on discrimination, identification and imitation of statements and questions that were characterized primarily by pitch direction differences in the final word. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
233
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(254 citation statements)
references
References 34 publications
19
233
1
1
Order By: Relevance
“…A harmonicity-based deficit would likely extend outside of music. Amusic deficits in prosody perception remain controversial (30,37), but our results suggest other domains where amusics and normal listeners may differ. Voice attractiveness, for instance, is positively correlated with the degree of harmonicity (52).…”
Section: Discussionmentioning
confidence: 57%
“…A harmonicity-based deficit would likely extend outside of music. Amusic deficits in prosody perception remain controversial (30,37), but our results suggest other domains where amusics and normal listeners may differ. Voice attractiveness, for instance, is positively correlated with the degree of harmonicity (52).…”
Section: Discussionmentioning
confidence: 57%
“…A recent study in our laboratory revisited the question of whether individuals with congenital amusia would show intact discrimination of contour in a linguistic context, taking care to consider the issues mentioned above (Liu et al, 2010). Our tone-analogues exactly mirrored the intonation patterns in speech; we used statement -question, as opposed to focus-shift sentence pairs, in order to remove any possibility of a semanticrecoding strategy being utilized in the speech condition, and we ensured that the speech stimuli (and thus the tone analogue stimuli) employed a range of pitch contrasts, including some that were more subtle than those that had been used in previous studies.…”
Section: The Quarterly Journal Of Experimental Psychologymentioning
confidence: 99%
“…These pitch deficits manifest as a difficulty in making fine-grained pitch discriminations (Foxton, Dean, Gee, Peretz & Griffiths, 2004;Hyde & Peretz, 2004;Jiang, Hamm, Lim, Kirk & Yang, 2011), processing pitch-change direction (Foxton et al, 2004;Liu, Patel, Fourcin & Stewart, 2010), and deciding whether two sequences of pitches are the same or different (Foxton et al, 2004;Hyde & Peretz, 2004;Jiang, Hamm, Lim, Kirk & Yang, 2010). Some studies have suggested that amusics may also have pitch memory deficits (Gosselin, Jolicoeur & Peretz, 2009;Tillmann, Schulze & Foxton, 2009), particularly with shorter tone spans (Williamson & Stewart, 2010).…”
mentioning
confidence: 99%
“…However, whether or not the musical pitch deficits in amusia also manifest as pitch-processing deficits in speech is currently debated. Some have argued that individuals with amusia do not have compromised interpretation and discrimination of Western speech intonation Peretz et al, 2002), whereas others have suggested that the pitch deficits in amusia extend to the processing of emotional prosody (Thompson, 2007) and speech intonation contours (including gliding-pitch analogues extracted from speech intonation; Hutchins, Zarate, Zatorre & Peretz, 2010;Jiang et al, 2010;Liu et al, 2010;Patel, Foxton & Griffiths, 2005;Patel, Wong, Foxton, Lochy & Peretz, 2008).…”
mentioning
confidence: 99%